HOW TO FIND A MARKET NICHE? - Pahlefy, Muhamad Reza; Wenedy, Aaron; Putri, Tasya Amanda (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
In today's competitive business landscape, identifying a market niche has become a critical strategy for companies seeking to differentiate themselves and build a loyal customer base. A market niche refers to a specific segment within a broader market, characterized by distinct needs, preferences, and challenges that remain underrepresented by mainstream competitors. This study provides a comprehensive framework for businesses to systematically identify and capitalize on market niches, ultimately gaining a competitive advantage. The research method used is a literature review, collecting and evaluating credible sources relevant to the topic. The findings reveal that identifying a market niche involves five key steps: identifying market needs and gaps, analyzing competitors, STP, evaluating the uniqueness of products or services, and validating the niche through market testing. The implications of this study provide practical insights for entrepreneurs and marketers in developing effective and sustainable niche marketing strategies while avoiding the risks of over-dependence on a narrow customer base or market saturation.